Perioperative Operating Room Efficiency Can Make Simultaneous Bilateral Total Hip Arthroplasty Cost-effective: A Proposal for a Value-sharing Model - Jeroen C.F. Verhaegen, MD; Alexina Schreiber, Ir; Clara Balust, Ir; Ayishwariya Menon, MEng; Jeroen Dille, Msc; Kristoff Corten, MD, PhD (Arthroplasty Today, 2022)
Background: Increasing demand for total hip arthroplasty (THA) and rising health-care costs have led hospitals to improve operating room (OR) efficiency. We compare the cost-effectiveness of a simultaneous bilateral THA to that of staged unilateral procedures following the implementation of OR efficiency strategies. Methods: Between 2017 and 2019, 446 simultaneous and 238 staged bilateral primary THA patients (mean age 61.3 ± 12.0 years; 41.8% males/58.2% females; mean body mass index 27.2 ± 4.8 kg/m2) were treated by a single surgeon using an efficient, standardized workflow for efficient direct anterior approach THA on a standard operating table. There were no differences in inclusion criteria between both groups. From this cohort, 16 simultaneous bilateral THAs and 34 unilateral THAs were prospectively compared for cost-effectiveness using detailed timestamp measurements and data on personnel and material usage. Outcome was assessed based on complication and reoperation rate and patient-reported outcome measures. Results: There was a complication rate of 1.2%, without a difference between patients who underwent a simultaneous THA vs those who underwent a staged primary THA (5/446; 1.1% vs 3/238; 1.3% P = .386). The mean OR time (patient in/out and turnover time) was 109.4 ± 19.8 minutes for bilateral THAs and 133.8 ± 12.8 minutes for 2 unilateral THAs (P < .001). An 18% time-saving and 14% cost-saving was achieved per procedure. Sharing 5% of the cost-saving with the surgeon brings benefit to both the hospital and surgeon. Conclusions: Implementing OR efficiency improves cost-effectiveness of simultaneous bilateral THA compared to unilateral procedures. A new value-sharing model could be a solution to align incentives.